Imagining Co-Immunity in Shadowpox: The Antibody Politic - Humphrey, Alison (Imaginations, 2020)
Shadowpox: The Antibody Politic is a game-based interactive installation that renders visible the forces our immunization decisions exert not just on our personal health but on the health of others. Part fact, part science fantasy, this full-body video game combines real-world statistical data with motion-tracking, live-animated digital effects to imagine a vaccine-preventable disease composed of viral shadows. The author explains how her initial design choices were rooted in a widespread misunderstanding: that our vaccination decisions have purely individual and private consequences. Once she became aware of her own blind spot, the game’s design, and the wider Shadowpox science fiction storyworld of which it was a part, came into focus, framing community immunity as a metaphor for the power we each have to make choices that will have a destructive or constructive effect on the world around us.